Subunit-Dependent Modulation of Kainate Receptors by Extracellular Protons and Polyamines - Mott, David D. (J Neurosci, 2003)
Synaptic activity causes significant fluctuations in proton concentrations in the brain. Changes in pH can affect neuronal excitability by acting on ligand-gated channels, including those gated by glutamate. We show here a subunit-dependent regulation of native and recombinant kainate receptors by physiologically relevant proton concentrations. The effect of protons on kainate receptors is voltage-independent and subunit dependent, with GluR5(Q), GluR6(Q), GluR6(R), and GluR6(R)/KA2 receptors being inhibited and GluR6(R)/KA1 receptors being potentiated. Mutation of two acidic residues (E396 and E397) to neutral amino acids significantly reduces the proton sensitivity of the GluR6(Q) receptor, suggesting that these residues influence proton inhibition. The endogenous polyamine spermine potentiated GluR6(R) kainate currents in a pH-dependent manner, producing an acidic shift in the IC(50) for proton inhibition. Spermine potentiation of GluR6(R) is voltage independent, does not affect receptor desensitization, and only slightly shifts the agonist affinity of the receptor. These results suggest that, similar to its action on NMDA receptors, spermine potentiates kainate receptors by relieving proton inhibition of the receptor. Furthermore, they suggest that fluctuations in brain pH during both normal and pathological processes could regulate synaptic transmission and plasticity mediated by kainate receptors.